A publicly verifiable protocol for random number generation - Penna, João; van de Graaf, Jeroen (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2017)
Chance plays an essential role in many decision procedures such as lotteries, draws etc. As such procedures are moving on-line, several web services offering randomness have appeared over the last few years. NIST’s randomness beacon, which publishes a sequence of 512 random bytes every minute, unfortunately lacks transparency: the beacon does not eliminate the possibility of an insider attack who knows the outcomes beforehand. We propose an improvement of NIST’s beacon which is publicly verifiable and fully transparent: any outsider who did not witness the bit generation in person but has internet access can convince himself that the beacon acted honestly, provided he can be sure that fresh, independent random bits were contributed to the seed value. Our proposal is based on a novel cryptographic assumption: the existence of functions that are slow to compute even on the fastest supercomputers.